Harassment towards Women in the Novel 'Perempuan yang Menangis kepada Bulan Hitam' by Dian Purnomo - Hilaria Heldiria Door; RM. Teguh Supriyanto,; Yusro Edy Nugroho (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The novel "Perempuan yang Menangis kepada Bulan Hitam" addresses the theme of sexual harassment experienced by a female character named Magi in a village in Sumba, which is rooted in a tradition called "kawin tangkap" or "yappa mawine." The aim of this study is to identify the types of sexual harassment committed against the female character in the novel "Perempuan yang Menangis kepada Bulan Hitam" by Dian Purnomo. The approach used in this research is feminist literary criticism. Data collection in this study is carried out using heuristic techniques. The collected data is then analyzed using hermeneutic techniques. The data in this novel consists of words, phrases, and sentences that contain information related to the research problem, extracted from the novel under study. The results of the research show that the sexual harassment experienced by the female character in the novel occurs both before and after marrying the perpetrator. The types of sexual harassment faced by the female character include gender harassment, seduction behavior, sexual bribery, sexual coercion, and sexual imposition.